Risk attitudes and digit ratio (2D:4D): Evidence from prospect theory - Levent Neyse; Ferdinand M. Vieider; Patrick Ring; Catharina Probst; Christian Kaernbach; Thilo van Eimeren; Ulrich Schmidt (Journal of Risk and Uncertainty, 2020)
Prenatal androgens have organizational effects on brain and endocrine system development, which may have a partial impact on economic decisions. Numerous studies have investigated the relationship between prenatal testosterone and financial risk taking, yet results remain inconclusive. We suspect that this is due to difficulty in capturing risk preferences with expected utility based tasks. Prospect theory, on the other hand, suggests that risk preferences differ between gains, losses and mixed prospects, as well as for different probability levels. This study investigates the relationship between financial risk taking and 2D:4D, a putative marker of prenatal testosterone exposure, in the framework of prospect theory. We conducted our study with 350 participants of Caucasian and Asian ethnicities. We do not observe any significant relationship between 2D:4D and risk taking in either of these domains and ethnicities.
Keywords: C91; D03; D81; D87; D91; 330; Prospect theory; Prenatal testosterone; Digit ratiio; Risk